Perancangan dan Pembuatan Sistem Informasi Perpustakaan Berbasis Web pada SMP YBPK 1 Surabaya - Abednego Abednego; Lily Puspa Dewi; Adi Wibowo (Jurnal Infra, 2017)
At this time the secondary school YBPK 1 Surabaya has to provide facilities for the library which is aimed at so that each student or teacher diligent reading the book. In the Junior Secondary School Library YBPK 1 Surabaya there are a number of facilities such as the lease the book, the return of the book, payment of fine and cabinet reference. Some discounted rates above is still done manually so that the officers of the library in trouble in recap transaction data. This application is created using HTML programming language, PHP, JavaScript, AJAX, Framework Codeigniter 3.0 and the MySQL database. The application display using the Bootstrap template. E-catalogue features using solr search engine is made in the Apache. Reminder features the return of the book using SMS Gateway Me template. The end result of the development of this application is able to search the list of book, can send reminder through SMS messages to prevent loan overdue, can record transaction with computerized library. Librarians can also view reports such as the report of fines, the visitor report, book assessment report and book donation report.Based on the results of questionnaires were obtained for display applications, 40% of respondents answered good, and 60% of respondents answered very well. For e-catalog feature, 40% of respondents answered not good enough, 20% responded good enough, and 40% of respondents answered good. For e-book feature, 20% of respondents answered enough, 40% said good, 40% responded very well. For book transactions feature, 20% of respondents answered enough, 20% responded good, and 60% of respondents answered very well. For a book proposal feature, 20% of respondents answered good, and 80% of respondents answered very well. To reserve features books, 40% of respondents answered not good enough, 20% of respondents answered good, and 40% of respondents answered very well. For the reminder feature the return of books, 20% of respondents answered enough, 20% of respondents answered well, and 60% of respondents answered very well. For ease of use, 20% of respondents answered enough, 40% of respondents answered good, and 40% of respondents answered very well. For compliance with requirements, 20% of respondents answered good, and 80% of respondents answered very well. For most applications, 40% of respondents rate the program was good, and 60% of respondents rate the program is very good.